The Contour Feathers of Cisticolae: Adaptations to Annual Rainfall - Klem, Jana le Roux; Bouwman, Hindrik; Rijke, Arie M. (Geography, Earth Science and Environment: Research Highlights Vol. 7, 2025)
This study has shown for the first time a correlation between the feather microstructure of land birds and the annual rainfall of their habitats that is shaped by the evolutionary forces of water repellency and resistance to water penetration. Birds of the genus Cisticola occur over most of Southern Africa in varying habitats ranging from low to high altitudes and wet to dry areas causing species to have unique distributions. In order to determine if Cisticolas have evolved species- specific water repellency and resistance to water penetration compatible with their habitats, we have measured the barb diameter and spacing of abdominal, breast and throat feathers of six cisticola species and related the results to mean annual rainfall and altitudes in five different locations. Water repellency was not significantly associated with altitude or maximum mean summer temperatures. However, water repellency increased markedly with annual rainfall in the 550 to 600 mm/year range for abdominal and breast feathers, but not for throat feathers. This increase was evident both among species occurring at multiple sites and among different species occurring at single sites. Food sources too will change with higher or lower rainfall. If climate change involves access to open water, further changes in feather structure may be expected such as presently seen in Dippers and shorebirds. However, the two species occurring at the wettest sites showed low water repellency, but increased resistance to water penetration. These findings suggest that water repellency and resistance to water penetration are part of the evolutionary forces that shape the microstructure of Cisticola contour feathers. Small changes in ramus width and spacing can alter a mostly water-repellent structure into one that is water resistant and vice versa. This feature represents a highly adaptive trait in the evolution of contour feathers for it enabled birds to colonize specific habitats and adopt specialized feeding habits.